Development and optimization of a double antibody sandwich ELISA for the detection of goose T cell surface CD8α molecule - Wei ZHANG; Bei-bei CHENG; Shun CHEN; Ming-shu WANG; Ren-yong JIA; De-kang ZHU; Ma-feng LIU; Fei LIU; Kun-feng SUN; Qiao YANG; Ying WU; Xiao-yue CHEN; et al. (Journal of Integrative Agriculture, 2016)
CD8, a glycoprotein on the surface of T cells, is involved in the defense against viral infection and plays significant roles in antigen presentation and in the antiviral immune response. CD8 is composed of two chains. Of these, the CD8α chain was chosen for the detection because it involved in both the CD8αα homodimer and the CD8αβ heterodimer. Here, we established a double antibody sandwich enzyme-linked immunosorbent assay (DAS-ELISA) for specific detection of goose CD8α (goCD8α). The results showed that the optimal coated antibody and antigen dilutions were 1:50 (the antibody titer was 1:12 800) and 1:32 (0.3 ng mL−1), respectively, while the optimal capture antibody and horseradish peroxidase (HRP)-labelled goat anti-rabbit IgG dilutions were 1:50 (the antibody titer was 1:51 200) and 1:4 000 (the antibody titer was 1:5 000), respectively. The optimal blocking buffer was 5% bovine serum albumin (BSA). The best incubating condition was overnight at 4°C, the best blocking time was 120 min and the best anti-capture antibody working time was 150 min. In addition, the minimum dose detectable by DAS-ELISA was 5×10−3 ng mL−1. Most importantly, goCD8α expression levels in goose spleen mononuclear cells (MNCs) post-Goose parvoviruse (GPV) infection were found to be significantly up-regulated using the DAS-ELISA method, which was consistent with previous results obtained using real-time quantitative PCR. In conclusion, the DAS-ELISA method reported here is a novel, specific technique for the clinical detection of goCD8α.